ChemInform Abstract: Metal‐Catalyzed Nitrile Hydration Reactions: The Specific Contribution of Ruthenium. Issue 3 (January 2015) - Garcia‐Alvarez, Rocio; Francos, Javier; Tomas‐Mendivil, Eder; Crochet, Pascale; Cadierno, Victorio
Abstract Review: 160 refs.